Ischemia modified albumin in perinatology. (March 2017) - Yarcı Gursoy, Aslı; Caglar, Gamze S.; Demirtas, Selda
Abstract: Ischemia modified albumin is a novel marker of ischemia generated due to hypooxygenation and increased hydroxyl free radicals in low pH. The molecule has been licenced for clinical use as an early marker for acute coronary syndrome in cardiology. Since presence of ischemia might have serious and sometimes devastating effects in perinatology, various researches have evaluated its value in different clinical conditions. This narrative review aims to summarize the literature concerning the value of IMA in perinatology and guide for further research.